ANALISIS PENGARUH BEBAN KERJA TERHADAP KINERJA PEGAWAI BADAN PUSAT STATISTIK (BPS) PROVINSI MALUKU - Sherly Rutumalessy (Jurnal Administrasi Terapan, 2023)
The Central Statistics Agency (BPS) has the task of providing quality statistical data and information: complete, accurate, up-to-date, sustainable and relevant to data users. Quality statistical data and information is a reference for policy formulation efforts in preparing plans, monitoring and evaluating programs so that the targets that have been set can be achieved precisely and effectively.This research aims to find out how workload affects employee performance. The analysis technique used is simple linear regression analysis to determine the extent of the influence of workload on employee performance.Based on the results of statistical tests, it can be clearly seen that the independent variable has an effect on the dependent variable. The influence given by the independent variable is negative, meaning that if there is a decrease in workload it will increase employee performance. Keywords: workload, employee performance